Integration of Nasal Cytology in Ayurvedic Diagnosis of Doshik Pratishaya A Pilot study - Swatika Sharma; Vaishali Deshpande; Shanti N. Dessai; Avinash S. Kande (The Bioscan, 2025)
Pratishyaya, a significant nasal disorder detailed in Ayurvedic texts, corresponds to various rhinitis forms in modern medicine. This study explores the diagnostic potential of nasal cytology in differentiating Pratishyaya types and correlates findings with Ayurvedic principles. Conducted as a prospective case-control study at Khemdas Ayurved Hospital, the research involved 10 participants divided into two groups: five clinically diagnosed Pratishyaya cases and five healthy controls. Nasal cytology samples were collected, processed, and analyzed to assess cellular patterns. The results revealed distinct cytological profiles among the subtypes. Kaphaja Pratishyaya showed high neutrophil counts, bacterial growth, and mast cell presence, indicating acute inflammation. Vataja Pratishyaya displayed a mixed eosinophilic and neutrophilic response, while Pittaja Pratishyaya exhibited moderate neutrophil infiltration with no eosinophilic or mast cell presence. Healthy controls demonstrated no inflammatory markers, confirming the specificity of nasal cytology. These findings highlight the utility of nasal cytology as a minimally invasive, precise diagnostic tool for Pratishyaya, aligning traditional Ayurvedic with contemporary classifications. While the study provides foundational insights, further research with larger cohorts and advanced technologies is recommended to validate and refine its diagnostic applications. Nasal cytology has the potential to revolutionize integrative healthcare for nasal disorders.